Looking Ahead, Looking Back: A Review of Works by 15 Artists Organised by Fergana Art Space (7th February–29th March 2015) - Abdullah, Sarena (Penerbit Universiti Sains Malaysia, 2015)
When it was announced through Facebook and email blasts that there will be an upcoming exhibition at Fergana Art Space, I looked forward to it as Fergana's previous exhibition on Ismail Hashim's photographic works was presented in an interesting and well-thought out curatorial manner. Although I missed the launching of the exhibition on 7th February 2015, I managed to visit the Looking Ahead: 15 Malaysian Artist exhibition a week later and even brought students from my class in mid-March, with Mr Ho Fan Choon, who is the Manager, giving us a guided tour of the exhibition.